2004
DOI: 10.2135/cropsci2004.0646
|View full text |Cite
|
Sign up to set email alerts
|

Production of γ-Linolenic Acid and Stearidonic Acid in Seeds of Marker-Free Transgenic Soybean

Abstract: and black currents (Ribes nigrum L.) (Goffman and Galletti, 2001). The yield potential of these herbs is Through a single desaturation step, the Borago officinalis L. ⌬ 6 rather limited and levels of GLA and STA in the seed desaturase can convert linoleic acid and ␣-linolenic acid to ␥-linolenic acid (GLA) and stearidonic acid (STA), respectively. Both GLA and storage lipids constitute Ͻ16 and 5%, respectively. STA are of interest to the pharmaceutical and nutraceutical industries.In plants, GLA is produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…Overexpression of Ostreococcus tauri Δ6-desaturase (Domergue et al, 2005) in transgenic camelina resulted in the accumulation of high levels of Δ6-desaturated fatty acids with 18% γ-linolenic acid (18:3 n-6, GLA) and 12% stearidonic acid (18:4 n-3, SDA) (Sayanova et al, 2011). The total level of non-native Δ6-desaturated fatty acids (30% of seed oil) was about twice that achieved using the same construct in Arabidopsis and compared well with previous attempts to synthesize these fatty acids in transgenic soybean (Sato et al, 2004;Eckert et al, 2006) and Brassica juncea (Hong et al, 2002) using phospholipid-dependent Δ6-desaturase activities. The potential of using acyl-CoA-dependent desaturases to enhance LC-PUFA production in camelina seeds was subsequently demonstrated.…”
Section: Fish Oil (Omega-3 Lc-pufas) Production In Camelinasupporting
confidence: 79%
“…Overexpression of Ostreococcus tauri Δ6-desaturase (Domergue et al, 2005) in transgenic camelina resulted in the accumulation of high levels of Δ6-desaturated fatty acids with 18% γ-linolenic acid (18:3 n-6, GLA) and 12% stearidonic acid (18:4 n-3, SDA) (Sayanova et al, 2011). The total level of non-native Δ6-desaturated fatty acids (30% of seed oil) was about twice that achieved using the same construct in Arabidopsis and compared well with previous attempts to synthesize these fatty acids in transgenic soybean (Sato et al, 2004;Eckert et al, 2006) and Brassica juncea (Hong et al, 2002) using phospholipid-dependent Δ6-desaturase activities. The potential of using acyl-CoA-dependent desaturases to enhance LC-PUFA production in camelina seeds was subsequently demonstrated.…”
Section: Fish Oil (Omega-3 Lc-pufas) Production In Camelinasupporting
confidence: 79%
“…Delta-6 desaturase genes from borage, Pythium irregulare, and Saprolegnia diclina have been seed specifically expressed in soybean, Brassicca juncea, and safflower (Carthamus tinctorius), with resulting GLA contents in the seed oil as high as 70% of total fatty acids Qiu et al, 2002;Sato et al, 2004;Knauf et al, 2006). Because most oilseed crops are predominantly omega-6 fatty acid-containing plants, it is necessary to express an omega-3 desaturase gene along with the delta-6 gene to produce SDA.…”
Section: Transgenic Oilseed Plants As Sources Of N-3 Fatty Acidsmentioning
confidence: 99%
“…The addition of antioxidant reagents such as L-cysteine and dithiothreitol has thus been shown to increase substantially the efficiency of transformation by this approach Somers 2001, Olhoft et al 2003). The bar gene has been widely applied as a selective marker in combination with glufosinate for the transformation of soybean cotyledonary node tissue (Zhang et al 1999, Paz et al 2004, Sato et al 2004, Zeng et al 2004, Paz et al 2006. Yun et al (2009) demonstrated the utility of the mat gene as a selective marker in Arabidopsis transformation and the PPT resistance in transformed rice calli harboring mat.…”
Section: Discussionmentioning
confidence: 99%